Change Is Hard: Adapting Dependency Graph Models For Unified Diagnosis in Wired/Wireless Networks - Bahl, Victor; Chandra, Ranveer; Maltz, David A.; Padhye, Jitu; Patel, Parveen; Ravindranath, Lenin; Maltz, Dave (Workshop: Research on Enterprise Networking, 2009)
Organizations world-wide are adopting wireless networks at an impressive rate, and a new industry has sprung up to provide tools to manage these networks. Unfortunately, these tools do not integrate cleanly with traditional wired network management tools, leading to unsolved problems and frustration among the IT staff. We explore the problem of unifying wireless and wired network management and show that simple merging of tools and strategies, and/or their trivial extension from one domain to another does not work. Building on previous research on network service dependency extraction, fault diagnosis, and wireless network management, we introduce MnM, an end-to-end network management system that unifies wired and wireless network management. MnM treats the physical location of end devices as a core component of its management strategy. It also dynamically adapts to the frequent topology changes brought about by end-node mobility. We have a prototype deployment in a large organization that shows that MnM’s rootcause analysis engine out-performs systems that do not take user mobility into account when localizing faults or attributing blame.